Preoperative Intravitreal Conbercept Facilitates Vitrectomy in Proliferative Diabetic Retinopathy: Is Attention Required for the Fellow Eye? - Wei Xu; Weijing Cheng; Yao Yao; Jian Guo; Guoxing Xu (Journal of Ophthalmology)
Purpose. To evaluate the effect of preoperative intravitreal conbercept (IVC) injection on patients with proliferative diabetic retinopathy (PDR). Methods. Medical records of patients who underwent vitrectomy due to complications of PDR were retrospectively reviewed. Patients were grouped as the IVC group and non-IVC group according to preoperative IVC. Preoperative, intraoperative, and postoperative data of both eyes were collected. The main outcome measures were best-corrected visual acuity (BCVA), intraocular pressure (IOP), central retinal thickness (CRT), and incidence of tractional retinal detachment (TRD). Results. A total of 37 cases were included, 16 in the IVC group and 21 in the non-IVC group. Preoperative IVC significantly reduced surgical duration (IVC vs. non-IVC, 88.9 ± 11.9 min vs. 97.8 ± 12.8 min, p < 0.05). In the vitrectomized eye, no significant difference existed between the IVC group and non-IVC group regarding postoperative BCVA (logMAR, 1.20 ± 0.53 vs. 1.27 ± 0.54, p = 0.68), IOP (16.5 ± 2.9 mmHg vs. 15.6 ± 3.7 mmHg, p = 0.44), and CRT (330.1 ± 35.2 μm vs. 319.2 ± 32.5 μm, p=0.34). In the fellow eye, 6 cases in the IVC group were diagnosed with TRD during postoperative follow-up, while only 2 cases were diagnosed in the non-IVC group (p < 0.05). Conclusion. Preoperative intravitreal injection of conbercept has effectively facilitated vitrectomy in PDR patients, but it potentially promotes tractional retinal detachment in the fellow eye following preoperative injection.